Prenatal-lactational alcohol exposure induces sex-specific CX3CL1/CX3CR1 dysregulation linked to neuroendocrine imbalance and cardiovascular risk - Medina-Vera, Dina; García-Bao, Alba; Medrano, Mireia; Martín-Chaves, Laura; Rodríguez-Capitán, Jorge; Rodríguez de Fonseca, Fernando; Serrano, Antonia; Jiménez-Navarro, Manuel Francisco; Valverde, Olga; Pavón-Morón, Francisco Javier (Elsevier, 2026)
Fetal alcohol spectrum disorder is associated with lasting neurodevelopmental and cardiovascular dysfunctions. The fractalkine axis CX3CL1/CX3CR1, a chemokine and its sole known receptor expressed in microglia and myeloid/endothelial cells, coordinates neuroimmune and vascular responses. We tested whether prenatal-lactational alcohol exposure (PLAE) is associated with sex-specific dysregulation of this axis along with integrated behavioral, neuroendocrine, inflammatory, and cardiovascular signatures. Pregnant C57BL/6 dams consumed 20% ethanol using a drinking-in-the-dark (DID) paradigm throughout gestation and lactation. Adult offspring (PND60–70) underwent behavioral testing (elevated plus maze and tail suspension test); plasma profiling of corticosterone, cytokines/chemokines, endothelial/coagulation markers, and matrix-remodeling enzymes; and cardiac transcriptional assays for stress- and inflammation-related genes (including Cx3cr1). Analyses were stratified by sex. PLAE females exhibited increased anxiety-like behavior, two-fold higher plasma CX3CL1, and upregulated cardiac Cx3cr1 compared with control females. PLAE males showed no behavioral or endocrine changes but evidence of matrix remodeling (elevated proMMP-9, reduced sP-Selectin). Across sexes, PLAE was associated with a proinflammatory/endothelial-activation profile (elevated IL13, IL18, and PAI-1, reduced CXCL16, higher proMMP-9) and altered cardiac expression of Nr3c2, Tnfrsf1a, Tlr4, and Nfkbia, compatible with early vascular risk. Independent of exposure, females exhibited reduced immobility and higher corticosterone, IL5, IL13, sE-Selectin, and thrombomodulin. Plasma CX3CL1 correlated inversely with exploratory and stress-coping behaviors, and positively with corticosterone, inflammatory/vascular markers, and cardiac Cx3cr1 and Tnfrsf1a. PLAE is associated with sex-specific dysregulation of the CX3CL1/CX3CR1 axis and convergent neuroimmune-vascular signatures indicative of subclinical endothelial dysfunction. These associative findings support the hypothesis that fractalkine-pathway modulation may mitigate long-term neurobehavioral and cardiovascular vulnerability after PLAE, warranting causal testing.
Keywords: Síndrome alcohólico fetal; Corazón - Enfermedades; Riesgos para la salud; Anxiety-like behavior; Cardiovascular risk; FASD; Fractalkine; Inflammation; PLEA; Sex differences; Stress